Achieving Education for All A Thought - Baid, Devesh (JOURNAL OF INDIAN EDUCATION, 2018)
A study of the management control policies and Class X grades of schools affiliated to a state board was conducted. The study revealed that the school fee the only significant variable explaining school performance. Since Colleman’s report, socio-economic status (SES) has been found as a significant variable explaining students’ performance. The society and the government have taken numerous steps to overcome this barrier to learning. The Right to Education Act 2009 was a milestone to achieve education for all strata of the society. The 25 per cent reservation in private schools for the lower income group has to be especially appreciated as this is a step towards inclusive education. But, this is not sufficient. Over time, we have realised that there is a need to do a little more. Residential schools, with the Public Private Partnership (PPP) model may be a way ahead to overcome the barriers of SES.